Fluorescence anisotropy of branched molecules containing 1-aminopyrene chromophores - Dvořák, Miroslav; Michl, Martin; Almonasy, Numan; Nepraš, Miloš; Ladd, Nemiah; Fidler, Vlastimil (Journal of fluorescence, 2011)
Fluorescence anisotropy measurements were performed on a set of multichromophoric compounds, which contain a different number of aminopyrenyl moieties linked to a triazine ring, in order to reveal the nature of both the electronic excited states and relaxation pathways of the compounds. Our experimental results complement quantum chemical calculations. We propose that the lowest excited state from which fluorescence proceeds is localized on a single individual aminopyrene moiety. In contrast, excitation to a higher excited state is likely followed by a migration of energy to another nearby aminopyrene chromophore before the internal conversion to the emitting state takes place. We suggest that this migration is responsible for the experimentally measured decrease of fluorescence anisotropy of the studied compounds.
Keywords: přenos energie; fluorescenční polarizace; Amines; Energy Transfer; Molecular Structure; molekulární struktura; Pyrenes; aminy; pyreny; Fluorescence Polarization